Students' Attitudes Towards Psychological Help-Seeking (Journal of Education and Development, 2020)
This study examined factors that may influence students' willingness to seek professional psychological help from the counselling services provided at a university. The study further investigated the relationship between sex, age, status of students (part-time, full-time), place of residence (urban, rural) and ethnicity and perceived barriers to seeking psychological help. The study used a sequential explanatory mixed methods research design conducted across two phases. In Phase One, a questionnaire survey was used to measure barriers to seeking professional help from a random sample of 925 students. In the second qualitative phase, focus group interviews were conducted with students to explore in a more in-depth way reasons put forward in the survey for not seeking professional psychological help. Statistical tests for the first phase were means, t-tests, ANOVA and Pearson Moment Product Correlation. Results showed that students viewed privacy, access, and trust issues as the most important barriers to seeking psychological help. There were also significant differences with regard to stigma, privacy and trust issues based on sex, age, year group, full-time/part-time status and ethnicity. Significant high to moderate correlations were found between all four factors. Qualitative findings supported factors examined in the first phase. However, other themes emerged such as lack of time, preference for solving one's own problems and preference for other sources of support.